1996
DOI: 10.3109/08037059609062118
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low Dietary Calcium Intake on Blood Pressure and Pressure Natriuresis Response in Rats: A Possible Role of the Renin-Angiotensin System

Abstract: Dietary Ca is an important modulator of blood pressure in humans and rats. Since the kidney plays a key role in the pathogenesis of hypertension, the effects of a low Ca diet (0.01% Ca) on blood pressure and pressure natriuresis response were studied in normotensive Sprague-Dawley rats. In addition, a possible role of the renin-angiotensin system in the development of hypertension and an altered pressure natriuresis response resulting from low dietary Ca intake was examined. In the low Ca diet group, systolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…A previous animal experiment using a hypertensive rat model reported that a high 2.5% Ca diet attenuated the development of hypertension or cardiac hypertrophy (39), and it was supported by the view that higher Ca supplementation reduces blood pressure by decreasing peripheral arterial resistance (40). Subsequently, elevating blood pressure has been considered as one of the risk factors of arterial calcification and stiffness (12,13). However, in this VDN rat model, we could not find any preventive effects of a high Ca intake on arterial Ca deposition.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A previous animal experiment using a hypertensive rat model reported that a high 2.5% Ca diet attenuated the development of hypertension or cardiac hypertrophy (39), and it was supported by the view that higher Ca supplementation reduces blood pressure by decreasing peripheral arterial resistance (40). Subsequently, elevating blood pressure has been considered as one of the risk factors of arterial calcification and stiffness (12,13). However, in this VDN rat model, we could not find any preventive effects of a high Ca intake on arterial Ca deposition.…”
Section: Discussionmentioning
confidence: 97%
“…According to several animal studies, an extraordinary low Ca intake around 0.01% induced an inhibitory effect on the pressure natriuresis response and increased sensitivity to the pressor response to angiotensin II, leading to the development of hypertension (12,13). Elevating blood pressure induced an arterial stiffening, reducing its distensibility, which was associated with an increased Ca content in the artery (14,15).…”
mentioning
confidence: 99%
“…Dietary calcium has been shown to have an effect on blood pressure in animal studies. Normotensive rats fed a free-calcium diet significantly increased their systolic blood pressure (SBP) between 15 to 35 mmHg in comparison with rats fed with normal calcium diet [4,5,6]. On the other hand, normotensive and hypertensive rats supplemented with calcium had significant lower values of SBP [7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…I ntraventricular hemorrhage (IVH) often occurs in premature infants and results in increased morbidity and mortality in survivors [1]. Intrauterine infection may predispose to IVH through inflammation [2].…”
Section: Abstract: Hmgb1 Intraventricular Hemorrhage Prematuritymentioning
confidence: 99%
“…ow dietary calcium intakes are related to conditions other than bone health, such as hypertension, with possible involvement of renin-angiotensin system [1]. Objective of this study was to explore association of dietary calcium intake and body composition with blood pressure (BP) in 10 -14 year-old Indian adolescents.…”
mentioning
confidence: 99%